Application of Rapid Application Development Method in Designing a Knowledge Management System to Improve Employee Performance in National Construction Company - Yumhi, Yumhi; Dharmawan, Donny; Desty Febrian, Wenny; Sutisna, Ade Jaya; Syahribulan (Jurnal Informasi dan Teknologi, 2024)
This research aims to learn how to create and implement a web-based knowledge management system to enhance worker productivity. This study uses literature reviews, interviews, and observation to collect data. The system development methodology used in the research was called Rapid Application Development (RAD). The study's findings suggest that knowledge management and documentation have significantly benefited from this research. The employee knowledge documentation process can be centrally and methodically recorded thanks to implementing the knowledge management system (KMS) used in this study. This improves the efficiency of the time spent conducting knowledge searches. The findings of this study allow staff members to log into the system directly. This technology will enable employees to organize, store, and transfer knowledge effectively. In line with the established key performance indicators (KPIs), having a knowledge management system improves employee performance overall. Employees can access knowledge from anywhere with flexibility when a web-based knowledge management system is implemented, thanks to MySQL database storage and PHP programming. Workers have access to and can contribute to the organization's information, which encourages high flexibility and supports worker mobility. In general, it is intended that the creation of this knowledge management system will serve as a valuable means of advancing knowledge management. Implementing this system is expected to increase employee productivity and performance while optimizing the use of knowledge owned by the company.